2020
DOI: 10.1038/s41598-020-61054-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption rate of Caenorhabditis elegans as a high-throughput endpoint of toxicity testing using the Seahorse XFe96 Extracellular Flux Analyzer

Abstract: Caenorhabditis elegans presents functioning, biologically relevant phenotypes and is frequently used as a bioindicator of toxicity. However, most C. elegans in vivo effect-assessment methods are laborious and time consuming. Therefore, we developed a novel method to measure the oxygen consumption rate of C. elegans as a sublethal endpoint of toxicity. This protocol was tested by exposing 50 larval stage one C. elegans individuals for 48 h (at 20 °C) to different concentrations of two toxicants i.e. benzylcetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…This showcases how bulk measurements are blind to single animal heterogeneities and that current OCR measuring methods are mostly reporting the middle body region respiration. The latter is important as, being a proxy for metabolic activity, OCR measurements are routinely used to assess toxicity of new substances [ [48] , [49] , [50] ]. If the tested substances have little impact on the middle body respiration but impact other regions, this would be hardly detected by bulk measurements.…”
Section: Resultsmentioning
confidence: 99%
“…This showcases how bulk measurements are blind to single animal heterogeneities and that current OCR measuring methods are mostly reporting the middle body region respiration. The latter is important as, being a proxy for metabolic activity, OCR measurements are routinely used to assess toxicity of new substances [ [48] , [49] , [50] ]. If the tested substances have little impact on the middle body respiration but impact other regions, this would be hardly detected by bulk measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of oxygen consumption is a vital marker indicating cellular function under normal or metabolically challenged conditions, including a fundamental indicator of mitochondrial function, reflecting on reactive oxygen species (ROS) production and metabolic activity during lifetime under normal or metabolically challenged conditions. Preez developed a novel method to measure the oxygen consumption rate of C. elegans and showed that the oxygen consumption rate is used as a promising functional measurement of toxicity (Preez et al, 2020). Respiration of C. elegans has also been used, although infrequently, to study the effect of toxicant exposure (Schouest et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In general (e.g., the dependent variable is cell viability), the value of u does not exceed 100% (the formula for cell viability determines the range of this value). Similarly, l was not less than 0% (20,21). In plan A (Table 1), u and l satisfy the conditions in the model (u ≤ 100% and l ≥ 0%).…”
Section: Dose Curves Of Dex For Wound Healing In Mice With and Withou...mentioning
confidence: 92%